Ação do ácido zoledrônico e do raloxifeno no colo femoral de ratas ovariectomizadas - Plazza, Flavia Alfredo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Some drugs, such as zoledronic acid and raloxifene are used for the treatment of bone diseases such as osteoporosis. The loss of bone mass is frequently observed in women after menopause due to decreased plasma estrogen hormone. The objectives of this study was to evaluate the performance of zoledronic acid (Zol) and raloxifene (Ral) in the femoral neck region of Wistar ovariectomized (OVX) and the association of action of these drugs. 50 rats of 6 months were used, and were divided into 5 groups: control, OVX/NaCl, OVX/Ral, OVX/Zol and OVX/Ral/Zol. It conducted the analysis of micro computed tomography (μCT), bone densitometry and mechanical testing. It was also performed the biochemical analysis to determine the plasma alkaline phosphatase activity (ALP) and tartrate-resistant acid phosphatase (TRAP). The results of μCT for cortical showed no significant differences. As for the trabecular, the OVX/NaCl group had lower bone mineral density, and drugs re-established these indices. The result also showed bone densitometry increase in bone mineral density in the groups receiving the treatments, while in OVX/NaCl this group decreased density. There were no significant differences in the analysis of maximum strength and stiffness of the neck. There was a decrease in the concentration of TRAP. However, the biomechanical analysis showed decrease of maximum strength in OVX animals. It concludes with this work that decrease in plasma concentration of estrogen in the body causes considerable loss of bone mass, and drugs like Zol and Ral are effective in the treatment, but when combined they do not potentiate

Alguns fármacos, como o ácido zoledrônico e o raloxifeno, são utilizados para o tratamento de doenças ósseas, como a osteoporose. A perda de massa óssea é observada frequentemente em mulheres na pós-menopausa, caracterizada pela diminuição plasmática do hormônio estrógeno. O objetivo deste estudo foi avaliar a atuação do ácido zoledrônico (Zol) e do raloxifeno (Ral) na região do colo femoral de ratas Wistar ovariectomizadas (OVX), bem como a ação da associação desses fármacos. Foram utilizadas 50 ratas de 6 meses, distribuídas em 5 grupos: Controle, OVX/NaCl, OVX/Ral, OVX/Zol e OVX/Ral/Zol. Foram realizadas análises de micro tomografia computadorizada (μCT), densitometria óssea e ensaio mecânico. Foi realizada também a análise bioquímica para determinação da atividade plasmática da fosfatase alcalina (FAL) e fosfatase ácida resistente ao tartarato (TRAP). Os resultados de μCT da região cortical do colo femoral não evidenciaram diferenças significantes. Já para o osso trabeculado da região de interesse, os animais do grupo OVX/NaCl apresentaram menor densidade mineral óssea, sendo esse índice restabelecido com os fármacos utilizados no estudo. Os animais OVX que receberam Ral associado ou não ao ZOL apresentaram diminuição na atividade de TRAP. As análises biomecânicas evidenciaram diminuição de força máxima nos animais OVX. Conclui-se com esse estudo que diminuição na concentração plasmática de estrógeno no organismo feminino adulto causa considerável perda da massa óssea, e fármacos como Ral e Zol são eficazes no tratamento, porém quando associados eles não se potencializam
Keywords: Osteoporose; Cloridrato de raloxifeno; Ratos; Osso e ossos; Osteoporosis